The antidepressants effects on microbiota: unobvious possibilities Research article - G. V. Rukavishnikov; L. V. Leonova; E. D. Kasyanov; N. G. Neznanov; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Despite the emergence of new antidepressants with different mechanisms of action, a large number of problems in antidepressant therapy remain. Considering the known antimicrobial activity of antidepressants, the role of the microbiota in the thymoanaleptic activity of these drugs is of high interest. In recent years, important data have been obtained on the role of the gut microbiota in the regulation of behavior and the pathophysiology of a number of mental disorders, including depression. Of particular interest is the assessment of the normal intestinal microbiota role in the course of the therapeutic process. The emerging bi-directional interactions between drugs and microorganisms may be critical for personalized drug selection and future drug development. However, at the present time, this problem remains poorly understood. The proposed manuscript articulates the main directions that are of clinical importance and can become an object for further study in this area.The research results indicate that the effect of antidepressants on the microbiota is a promising area, the study of which could provide many important findings for clinical practice. This type of therapeutic manipulation can provide an opportunity for intervention in order to potentiate the activity of antidepressants or to minimize side effects. The problem with this method of intervention is enormous complexity, when manipulations can have both positive and negative effects simultaneously, depending on different strains of microorganisms influencing different therapeutic effects. More research is needed to understand what changes occur in the microbiome with acute and chronic administration of specific antidepressants. Perhaps this will contribute to the development of microbiomodulatory tactics for individualized interventions.